Microstructural, surface morphological, and magnetic properties of oblique angle deposited Co thin films on ion-beam fabricated self-organized Si substrates - Patel, Shiv P.; Basu, T.; Kumar, M.; Mishra, P.; Som, T. (Materials Letters, 2022)
The microstructural, surface morphological, and magnetic properties of Co thin films grown, under oblique angle deposition, on low energy (500 eV) ion-beam fabricated self-organized rippled-Si substrates are presented. All films show the hexagonal-close-packed structure with the majority of the Co grains oriented along the (101‾2) and (0002) directions. Interestingly, Co film morphology follows the underlying ripple topography up to a thickness of 15 nm, whereas the conformal growth disappears at higher thicknesses (viz. 30 and 60 nm). The thicker films show the signature of tilted columnar structures. Further, a strong uniaxial magnetic anisotropy is observed for all films with the easy axis of magnetization perpendicular to the direction of the ripple wave vector.
Keywords: Co thin films; Hexagonal closest packed structures; Lower energies; Magnetic properties of co; Micro-structural; Oblique angles; Oblique-angle deposition; Rippled-si; Self-organised; Si substrates; Co thin film; Magnetic anisotropy; Oblique angle deposition; Rippled-Si